In-silico and in-vivo comparative evaluation of the cardioprotective potential of Yellow turmeric and White turmeric in Mn-induced cardiac oxidative stress - Toluwalope T. Fasooto; Oluwakemi R. Ogundana; Abiola F. Adebayo; David B. Olawade; Ezekiel A. Olugbogi; Oluwaseun Fapohunda; Afolabi C. Akinmoladun (Elsevier, 2024)
Introduction: The effect of the ethanol extracts of Curcuma longa Linn (yellow turmeric) and Curcuma zedoaria Rosc (white turmeric) on cardiac oxidative stress in rats exposed to manganese was evaluated in this study. Methods: We divided 60 Wistar rats into 12 groups (n = 5) with some administered different concentrations of yellow or white turmeric extract. The animals except the control groups were exposed to manganese on days 1,3, and 7. All the animals were sacrificed on the 8th day and the hearts were harvested for biochemical assays. Ferric-reducing antioxidant power (FRAP) and the levels of cardiac superoxide dismutase, reduced glutathione, nitric oxide, and lipid peroxidation in rats were determined. Additionally, in silico studies were performed to further compare the cardioprotective potential of the two species of turmeric. Results: The results showed that rats treated with manganese alone had decreased levels of FRAP, superoxide dismutase, and glutathione but increased levels of nitric oxide and lipid peroxidation were observed. The Mn-induced oxidative stress was ameliorated in animals co-treated with yellow or white turmeric. The yellow turmeric showed better activity than white turmeric. In the in-silico evaluation, phytocompounds from yellow turmeric had higher binding energy against Nuclear factor erythroid 2-related factor 2 (NRF2) protein than the ones from white turmeric. Bioactive compounds from white turmeric did not violate any of Lipinski's rules of five or three, despite having lower binding energy. Conclusion: These findings suggest that ethanol extract of yellow and white turmeric may have the potential to ameliorate manganese-induced cardiac oxidative stress.